Aplikasi Coat dan Film Pati Batang Aren untuk Mencegah Susut Berat dan Pencoklatan pada Buah Apel Terolah Minimal - F. Sinung Pranata (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
Minimally processed fruits provide convenience and freshness characters. Weight loss is a critical factor affecting the shelf life of minimally processed apples. These apples were limited by brown coloration that develops on surface. The objective of this study is to evaluate the effectiveness of edible coat and film made from aren starch against weight loss and browning on minimally processed apples. Edible coat and film solutions were prepared from 3% (w/v) aren starch, 6% (w/w) palmitic acid, and 1% (w/v) sorbitol. Minimally processed apples were either dipped in the coating solution or wrapping by edible film and then stored at ambient temperature for 8 hours. Browning appearance was determined every 4 hours and weight loss of apples was measured every hour.  Edible film was much effective on weight loss control than coating during storage. Color analysis showed that pati aren edible  coating and film wrapping did not significantly delayed browning reaction on  minimally processed apples.